Impact of periprocedural myocardial injury after transcatheter aortic valve implantation on long-term mortality: a meta-analysis of Kaplan-Meier derived individual patient data - de Sá Marchi, Mauricio Felippi; Calomeni, Pedro; Gauza, Mateus de Miranda; Kanhouche, Gabriel; Ravani, Lis Victória; Rodrigues, Caio Vinicius Fernandes; Tarasoutchi, Flávio; de Brito, Fábio Sandoli; Rodés-Cabau, Josep; Van Mieghem, Nicolas M.; Abizaid, Alexandre; Ribeiro, Henrique Barbosa (Frontiers in Cardiovascular Medicine, 2023)
Background: Periprocedural myocardial injury (PPMI) frequently occurs after transcatheter aortic valve implantation (TAVI), although its impact on long-term mortality is uncertain.We performed a pooled analysis of Kaplan-Meier-derived individual patient data to compare survival in patients with and without PPMI after TAVI. Flexible parametric models with B-splines and landmark analyses were used to determine PPMI prognostic value. Subgroup analyses for VARC-2, troponin, and creatine kinase-MB (CK-MB)-defined PPMI were also performed.Eighteen observational studies comprising 10,094 subjects were included. PPMI was associated with lower overall survival (OS) after two years (HR = 1.46, 95% CI 1.30 -1.65, p < 0.01). This was also observed when restricting the analysis to overall VARC-2-defined PPMI (HR = 1.23, 95% CI 1.07 -1.40, p < 0.01). For VARC-2 PPMI criteria and VARC-2 troponin-only, higher mortality was restricted to the first 2 months after